A Movement's Legacy: Southern Echo and the Continued Struggle for Racial Justice in the Delta. Issue 1 (2nd January 2016) - Tieken, Mara Casey; Warren, Mark R.
Abstract : Recent research has complicated popular understandings of the civil rights movement, calling into question its timeline, key players, and biggest victories. Scholars have highlighted the role of community organizing, arguing that capacity-building and leadership development were the movement's real wins. Yet little research has examined how contemporary organizers view and use this history in their current work. Drawing upon interview and observational data from a qualitative case study, this article explores how one Delta organization, Southern Echo, responds to the movement of the 1950s and 1960s in its organizing today. We argue that Echo organizers and leaders see the civil rights movement as an ongoing struggle, and we show that Echo adopts a critical stance in analyzing past civil rights work; Echo's structure and strategies are a direct response to this history. Our analysis offers a new, critical perspective to understandings of the civil rights movement.